2015
DOI: 10.1134/s0015462815020118
|View full text |Cite
|
Sign up to set email alerts
|

Application of the method of invariant relations in analyzing the parametric dependences of the aerodynamic parameters of the classical axisymmetric noses of flight vehicles

Abstract: The method of invariant relations rigorously validated under the conditions of "local mechanical interaction" is applied to the derivation of approximate formulas for calculating the aerodynamic parameters of axisymmetric flight vehicles, whose generators represent combinations of rectilinear and ogive-shaped sections, on a basis of three canonical vehicle shapes with the same mid-sections in reduced coordinates. These are the circular disk, the spherical segment, and the sharp circular cone tangent to the seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previously, the effects of spike on flow structure around the nose and drag reduction were studied widely by both experimental and numerical approaches [2][3][4][5][6][7][8][9]. Stalder and Nielsen [1], who conducted measurements with spikes at high Mach number, indicated that aerodynamic drag of the model decreases with increasing length up to two times of diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the effects of spike on flow structure around the nose and drag reduction were studied widely by both experimental and numerical approaches [2][3][4][5][6][7][8][9]. Stalder and Nielsen [1], who conducted measurements with spikes at high Mach number, indicated that aerodynamic drag of the model decreases with increasing length up to two times of diameter.…”
Section: Introductionmentioning
confidence: 99%